Il caso Cappato tra Corte Costituzionale, Parlamento e dibattito pubblico. Un breve appunto per una discussione da avviare (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The article analyses the ordinance n. 207/2018 of the Constitutional Court (about the Cappato - Fabio Antoniani - Dj Fabo case) as well as the previous sentences where it comes from. The constitutional legitimacy of Article 580 of the Penal Code had been doubted, since it incriminates both the instigation and the help to suicide in the same way, without introducing any distinction (in the second case) between moral and material help and (in the latter hypothesis) between direct help or not decisive facilitation and, plus, without taking into account some special cases (serious physical suffering of the suicidal aspirant, who asks to be freed from it). The Court invited the Parliament to take a decision on this matter, before giving its last word at a hearing already scheduled - if necessary - for the month of September 2019.
Keywords: Bioethics; Self-determination; Assisted suicide; Constitutional review; Parliamentâ€™s â€œexpressiveâ€ function